Enlighten…Camera…Action…Apply! Using Participatory Pedagogies to Promote Student Experiences of Social Emotional Learning in Physical Education - Howley, Donal; Dyson, Ben; Baek, Seunghyun; Fowler, Judy; Shen, Yanhua (The Canadian Journal of Action Research, 2026)
The purpose of this study was to explore secondary/high school students’ enactment of participatory pedagogies promoting experiences and understandings of Social and Emotional Learning (SEL) in Physical Education. Forty-two ninth and tenth grade students (30 female, 12 male) aged 14–16 participated in data collection, with inductive and deductive data analysis applied. Utilizing participatory pedagogies and action research led to an explicit and intentional focus on SEL that enhanced students’ understanding and appreciation as to how emotions, behaviors, social roles, and responsibilities influenced their participation in physical activity within and beyond physical education settings. The promotion of SEL competencies and skills in physical education through action research and participatory pedagogies that align with a contemporary framework can support secondary/high school students in attaining knowledge, skills, and attitudes for pursuing a physically active lifestyle and a lifetime of autonomous wellbeing.